Nutritional Value of Fermented Palm Oil Fronds as a Basis for Complete Feed for Ruminants - Astuti, T.; Santoso, U.; Amir, Y. (Pakistan Journal of Nutrition, 2017)
Objective: This study aimed to evaluate the nutritional value of a complete feed based on palm oil fronds fermented with microorganisms derived from rumen contents. Methodology: This study used a completely randomized design. The five feed treatment groups with 3 replicates were used. One group was complete feed containing 30% field grass+10% fermented palm oil frond+60% concentrate (R1), the other groups were 20% field grass+20% fermented palm oil frond+60% concentrate (R2), 10% field grass+30% fermented palm oil frond+60% concentrate (R3), 0% field grass+40% fermented palm oil frond+60% concentrate (R4) and 20% field grass+20% palm oil frond+60% concentrate (R5). Results: The experimental results show that the feed treatments significantly affected the contents of dry matter, organic matter, acid detergent fiber, hemicellulose and the digestibility of the dry matter (p<0.05) but had no effect on ash, crude fiber, crude protein, crude fat, neutral detergent fiber, lignin and cellulose (p>0.05). The treatments significantly (p<0.05) affected feed efficiency but had no effect on the average daily gain or feed consumption (p>0.05) in Kacang goats. Conclusion: It was concluded that palm oil fronds could be used as forage for Kacang goats.